Peningkatan Motivasi Berprestasi Bagi Santri Melalui Metode Peer Teaching di Pondok Pesantren Ar-Rohmah Grobogan - Moh Farhan; Susiyanto Susiyanto; Sukijan Athoillah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
Learning motivation has a position that is quite urgent in supporting the success of the learning process. In general, the problems faced by students who study in two educational institutions such as the world and pesantren, in the case raised in the community service, are low motivation to learn and low time management. Learning activities using the Peer Teaching method turned out to make a positive contribution to improving achievement motivation among students of the Ar-Rohmah Grobogan Islamic Boarding School. Education that involves peers as supervisors and supervisors can also create a conducive and pleasant learning environment. However it is not without challenges at all. Mass media such as television and increasingly open internet access are problems that must be solved in the future so that the atmosphere of santri learning can be better conditioned